The role of dynamic smart lighting in shaping the mood and functionality of interior spaces Contemporary (Comprehensive Journal of Science, 2026)
Lighting is a fundamental element of interior design, influencing the form and function of spaces, as well as the psychological and emotional atmosphere of users. With technological advancements, smart, dynamic lighting systems have emerged, allowing for control over light intensity, color, and timing to align with user needs and the nature of the activity. This study aims to explore the impact of smart, dynamic lighting on the mood and functional performance of users in contemporary residential, educational, and administrative spaces, focusing on the balance between aesthetics, functionality, and psychological comfort. The research employed a descriptive-analytical approach, utilizing tools such as questionnaires and field observations, and descriptive and statistical data analysis to compare spaces equipped with smart lighting with traditional spaces. The results demonstrated that smart, dynamic lighting improves mood, increases focus and productivity, reduces eye strain, and enhances visual comfort. It also highlights architectural elements and adds aesthetic appeal to spaces. Furthermore, the study revealed a gap between the technical capabilities of smart lighting and its practical application, underscoring the need for its systematic integration to achieve a healthy, comfortable, and functional indoor environment.
Keywords: Dynamic Smart Lighting, Interior Spaces, User Experience.